TOLERANSI SEBAGAI PILAR: PERAN ISLAM DAN KRISTEN DALAM MEMBANGUN MASYARAKAT MULTIKULTURAL - Selviana Veronika Moruk; Alise de Fatima Noronha; Frederico de Araújo Quintão (Al Naqdu, 2025)
This article examines the role of Islam and Christianity in building a multicultural society through the perspective of tolerance. With a literature study approach, this article analyzes the history of the relationship between Islam and Christianity, the concept of tolerance in both religions, the practice of tolerance in historical and contemporary contexts, the challenges and obstacles in building tolerance, and the factors influencing tolerance. Key findings show that tolerance is a fundamental value in Islam and Christianity, reflected in sacred teachings and historical examples. The practice of tolerance in a variety of contexts shows great potential for building harmony, although challenges such as religious extremism, prejudice, and inequality remain. This article concludes by reaffirming the importance of tolerance in multicultural societies and recommending further research on the role of religious leadership, the influence of education, and identity dynamics in promoting interfaith harmony